MANAJEMEN KESISWAAN DALAM MENINGKATKAN KEDISIPLINAN SISWA DI SMAN 4 BERAU - Ahmad Syaddad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Student management is one of the management that has a great influence on the formation of discipline attitudes in schools, because student management is a control of various types of student activities, one of which is related to discipline development. Discipline in school means obeying the rules or regulations that already exist in the school. For example, arrive on time, wear clothes that are according to the rules and neat, follow ceremonies and others. In this case, researchers will discuss student management in improving student discipline at SMAN 4 Berau. Discipline in the school is quite strict such as entering school at 06.30, participating in teaching and learning activities, participating in congregational prayers, collecting electronic media such as cellphones that are not used for learning and others. But there are still students who are not disciplined such as arriving late, in this case the guidance teacher will give punishment to students who arrive late such as reading asmaul khusna before attending the lesson. The purpose of this study is to determine student management in improving discipline in SMAN 4 Berau schools. This research method uses qualitative methods. This data collection technique is through interviews, observation, and documentation.